2019
DOI: 10.1249/01.mss.0000562533.51911.d4
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health in Elite Norwegian Endurance Cyclists and Runners: A Cross-Sectional Study

Abstract: What are the new findings? ► Elite road cyclists have lower bone mineral density (BMD) compared with middle-distance and long-distance elite runners, despite performing lower limb heavy resistance training. Ten of 19 cyclists were classified with low BMD. ► Low BMD was evident in male and female cyclists and affected the lumbar spine and the femoral neck. ► Type of sport was the only independent variable associated with low BMD. How might it impact on clinical practice in the near future? ► Our finding of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Relative energy deficiency in sport (RED-S), a common phenomenon, can be detrimental to improvement and overall health in sport [20], which may negatively impact BMD in both sexes [21]. Energy availability has shown correlations with vitamin D levels, which may be relevant for bone health [22]. Low BMD is a risk factor for stress fractures, a particular risk for elite athletes of either sex whose careers may be ended prematurely as a result of injury [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative energy deficiency in sport (RED-S), a common phenomenon, can be detrimental to improvement and overall health in sport [20], which may negatively impact BMD in both sexes [21]. Energy availability has shown correlations with vitamin D levels, which may be relevant for bone health [22]. Low BMD is a risk factor for stress fractures, a particular risk for elite athletes of either sex whose careers may be ended prematurely as a result of injury [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested that elite sport participation may have contemporaneous benefits for bone health [22,[27][28][29], this review has highlighted the paucity of research data available regarding this important topic. Longitudinal studies are required, with consideration given to menstrual status in females and vitamin D status in all athletes.…”
Section: Discussionmentioning
confidence: 99%